The structure of a major surface antigen SAG19 from Eimeria tenella unifies the Eimeria SAG family - Nur Zazarina Ramly; Samuel R. Dix; Sergey N. Ruzheinikov; Svetlana E. Sedelnikova; Patrick J. Baker; Yock-Ping Chow; Fiona M. Tomley; Damer P. Blake; Kiew-Lian Wan; Sheila Nathan; David W. Rice (Springer Nature, 2024)
Indexed by Scopus